Запозичення з польської мови в буковинських говірках (на матеріалі говірки с. Южинець Кіцманського р-ну Чернівецької області). - Руснак, Наталія Олександрівна; Струк, Іванна Михайлівна (Дрогобич: Видавничий дім «Гельветика», 2022)
The article analyzes borrowings from the Polish language in Bukovynian dialects (based on the dialect of Yuzhynets village, Kitsman district, Chernivtsi region), the vocabulary of which preserves the nation’s original worldview, relics of spiritual culture, understanding of ethical norms, relations with other peoples, reproduces socio-political changes in the society. Analysis of the vocabulary of dialects allowed us to draw conclusions about the main trends in the lexical system of language. Based on the Etymological Dictionary of the Ukrainian Language, the Dictionary of Bukovinian Dialects and the Dictionary of the Ukrainian Language, the origin of dialectismsPolonisms is clarified and the way of their semantic and structural development is determined. The urgency of the research is caused by the need to study the spoken language, in particular the vocabulary of Bukovinian dialects which allows to touch the sources of national memory, to comprehend the historical path of Bukovinian people. Yuzhynets village, Kitsman district, Chernivtsi region singled out several groups of Polish dialects in the lexical system of speech: 1) words borrowed from the Polish language with the same meaning, among them names adapted to the lexical-semantic system of dialects (there were semantic shifts in the meanings of dialectisms-Polonisms); 2) borrowed words (from German, Latin, French), for which the Polish language acts as a mediator. It is noted that Polish words become creative for derivatives, the meanings of dialectismsderivatives are formed on the basis of associative connection with the meaning of creative-Polonisms. It is proved that dialectisms-Polonisms adapt to the phonetic-grammatical system of speech. Lexical and semantic adaptation of names in Bukovinian dialects concerns both the donor language and the intermediary language. In addition, among the borrowed vocabulary in Bukovinian dialects, borrowings from European languages, were recorded which, in turn, inherited them from Latin and became a source of replenishment of the dialect vocabulary of the Ukrainian language. It is stated that dialectisms-Polonisms of the dialect Yuzhynets belong to different parts of speech, which form the main lexical and semantic groups.
Borrowing from the Polish language in Bukovynian dialects (on the material of the dialect of the village of Yuzhynets, Kitsman district, Chernivtsi region
Keywords: borrowed words; dialectism; Polonism; dialect; lexical system of language